The impact of tricyclic antidepressants and selective serotonin re-uptake inhibitors on handwriting movements of patients with depression - Tucha, Oliver; Aschenbrenner, Steffen; Eichhammer, Peter; Putzhammer, Albert; Sartor, Heino; Klein, Helmfried E.; Lange, Klaus W. (Psychopharmacologia, 2002)
Psychomotor retardation is a common symptom of patients with major depressive disorder. While a variety of clinical examinations using different techniques have been undertaken to assess the motor component of psychomotor retardation in depression, the effects of antidepressants on psychomotor functions have been examined less extensively. The aim of the present study was to examine the effect of various pharmacological treatments on handwriting movements of patients with depression. Kinematic data of automated handwriting movements of 18 depressed patients receiving tricyclic antidepressants (TCAs), 18 patients on selective serotonin re-uptake inhibitors (SSRIs) and 18 healthy subjects was recorded and analysed. Groups were matched according to age, sex, handedness and education level. For the assessment of fine motor movements, a digitising tablet was used. Subjects were asked to perform a simple writing task. Movement time, velocity and acceleration of the handwriting movements were measured. Statistical analysis of writing movements revealed motor slowing in patients receiving TCAs. In comparison with both healthy subjects and patients receiving SSRIs, the TCA group displayed an increased movement time, reduced automation of handwriting, lower maximum velocities and reduced acceleration of descending strokes. The results suggest either that TCAs have adverse effects on motor functioning or that they are less effective in the treatment of motor retardation than SSRIs.